RFID for the Supply Chain and Operations Professional. - Zelbst, Pamela J. (Business Expert Press, 2021)
This book will help readers develop an understanding of the capability of the technology to increase an organization's customer responsiveness. In the third edition, the discussion and examples have been updated to reflect the rapid advancement in RFID technology. A new case study and new examples have been added along with updated discussions and projections about RFID technology.